Pistacia integrrima Stewart ex Brandis: a less known high value medicinal plant - Bharti Sharma,; Sheezan Rasool,; Shreekar Pant, (International Journal of Phytomedicine, 2017)
The family Anacardiacea, best represented by the species Pistacia integrrima Stewart ex Brandis, is known worldwide for its manifold uses. It is widely used to cure various diseases like cold, cough, asthma, fever, vomiting and diarrhea, etc., and widely used in modern medicine. Therefore, an attempt has been made to assess the medicinal potential of the species both in traditional as well as in modern medicine system. These properties are supposed to be cured by different active compounds present in the plant. This paper provides the relevant information about medicinal properties of this high value medicinal plant.